2014
DOI: 10.1071/wr13136
|View full text |Cite
|
Sign up to set email alerts
|

First in, first served: uptake of 1080 poison fox baits in south-west Western Australia

Abstract: Context: In Western Australia, baits containing 1080 poison are widely used to control the red fox (Vulpes vulpes) for fauna conservation. Despite long-term (15-17 years) baiting programs, bait uptake by target and non-target species is largely unknown, but affects baiting efficacy. Aims:We examined bait uptake of 1080-poisoned fox baits laid according to current practice at seven riparian sites in the northern jarrah forest (of south-west Western Australia). There, intensive baiting regimes have been implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Berry et al 2013), the possibility of avoidance of baits by foxes has also been raised by various authors (e.g. van Polanen Petel et al 2001;Dundas et al 2014). Innate avoidance of baits can be selected for over successive baiting runs, which will quickly remove bold/explorative individuals from the population, rapidly shifting the population average towards more neophobic animals.…”
Section: Control Of the Red Fox In Australiamentioning
confidence: 99%
See 4 more Smart Citations
“…Berry et al 2013), the possibility of avoidance of baits by foxes has also been raised by various authors (e.g. van Polanen Petel et al 2001;Dundas et al 2014). Innate avoidance of baits can be selected for over successive baiting runs, which will quickly remove bold/explorative individuals from the population, rapidly shifting the population average towards more neophobic animals.…”
Section: Control Of the Red Fox In Australiamentioning
confidence: 99%
“…animals not previously exposed to persecution/baiting, and/or consisting of predominantly yearling dispersers), suggesting that long-term programs, using the same approach consistently, artificially select for innate bait avoidance traits in red foxes. Dundas et al (2014) reported foxes passing baits on camera on multiple occasions, suggesting that, even though they had located baits, they did not take them. A similar finding has been reported by Kinnear et al (2017).…”
Section: Control Of the Red Fox In Australiamentioning
confidence: 99%
See 3 more Smart Citations